Reading in the city: mobile eye-tracking and evaluation of text in an everyday setting - Chana, Kirren; Mikuni, Jan; Schnebel, Alina; Leder, Helmut (Frontiers in Psychology, 2023)
Reading is often regarded as a mundane aspect of everyday life. However, little is known about the natural reading experiences in daily activities. To fill this gap, this study presents two field studies (N = 39 and 26, respectively), where we describe how people explore visual environments and divide their attention towards text elements in highly ecological settings, i.e., urban street environments, using mobile eye-tracking glasses. Further, the attention towards the text elements (i.e., shop signs) as well as their memorability, measured via follow-up recognition test, were analysed in relation to their aesthetic quality, which is assumed to be key for attracting visual attention and memorability. Our results revealed that, within these urban streets, text elements were looked at most, and looking behaviour was strongly directed, especially toward shop signs, across both street contexts; however, aesthetic values were not correlated either with the most looked at signs or the viewing time for the signs. Aesthetic ratings did however have an effect on memorability, with signs rated higher being better recognised. The results will be discussed in terms aesthetic reading experiences and implications for future field studies.